Diagnósticos de Enfermagem identificados na admissão hospitalar de idosos, para tratamento de doenças crônicas não transmissíveis. - GUEDES, Helisamara Mota (2007)
In accordance with the necessity of rethinking the nurse performance towards to the health program of elderly people, it appears the necessity of knowing these people human answers at the moment of the hospital admission. The nursing diagnostic knowledge will allow the assistance planning to these aged ones, and also, to prepare the nursing team to attend these answers. Objectives: to analyze these population characteristics such as: age, sex, occupation, education, civil state, religion, monthly income, number of children, origin, number of chronic illnesses, ways of admissions to the hospital and previous internments, according to their gender; to identify in accordance to the Taxonomy of NANDA (2006) Nursing Diagnostic among the interned ones for clinical treatment; to describe the related factors of risk and defining characteristics of the identified diagnostic of nursing in this population. Methodology: it is related to a descriptive study, quantitative boarding, in 28 aged ones admitted during the first 24 hours in the medical clinic, situated in a center-west region Hospital School. The data collection occurred between August to October, 2007, by means of an instrument usage, half-structuralized for the elderly people evaluation. For the identification of the nursing diagnostic, the process of clinical reasoning in accordance with Risner (1995) was used. Results: People admitted into the medical clinic had presented as characteristic to be predominantly men, aged group in between 60 to 69, Catholics, low education, monthly income of one to three minimum wages, carrying two or more illnesses, 85.7% with previous internments and 57.1% admitted by the Ready Aid. Among these numbers, 58 different nursing diagnosis had been identified, variation of 8 to 18 diagnostic, average of 12.36, shunting line standard of 2.94 and medium of 12. The domain Activity/Rest, Elimination and Exchange and Perception/Cognition, had presented greater prevalence of nursing diagnosis. The domain Life Principles and Growth/Development had not presented nursing diagnosis. The domain Security/Protection and Confrontation/Toleration to the Stress had presented a low prevalence if compared to the other domains. The diagnostics which have had bigger frequency of 50% were: harmed dentition (100%), risk for infection (100%), deficit knowledge (82.1%), disposal for improved self-concept (82.1%), disposal for improved familiar processes (72.5%), disposal for increased individual confrontation (60.6%) and risk for falls (57.1%). The diagnostics which have had less frequency of 3.5% were: fluid volume excess, altered nutrition: less than body requirements, constipation, risk for constipation, feeding self care deficit, rambling, disposal increased for knowledge concerning the illness, impaired memory, impaired verbal communication, risk of impotence feeling, situational low self esteem, body image disturbance, hyperthermia and social isolation. The most prevalent related factors to these nursing diagnostic prospects were weakness/fatigue, metabolic alterations, chronic illness, harmed cognition, disequilibrium between offer and demand of oxygen, the risk factors were the medicine usage, energy decrease/fatigue, presence of circulatory/respiratory problems. Conclusion: The present study had provided the knowledge of which are the elderly care necessities and also to supply subsidies so that the related hospital nursing team can base the assistance, planning an holistic and resolutive care, as well as making possible the adequacy of the human resources and material to attend the demand